2007
DOI: 10.1029/2007ja012573
|View full text |Cite
|
Sign up to set email alerts
|

Spectral features of SKR observed by Cassini/RPWS: Frequency bandwidth, flux density and polarization

Abstract: [1] We report on an analysis about the spectral shape of the Saturnian kilometric radiation (SKR) recorded by the RPWS/HFR experiment onboard the Cassini spacecraft. The SKR envelope is found to be very variable in timescales covering a large range, from hours to days. Despite this change, we proceed to a classification of the shape in the frequency range from 3.5 kHz to 1.2 MHz taking into consideration the phenomenology and the state polarization of the radio wave. In the considered SKR bandwidth, we make a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 17 publications
1
38
2
Order By: Relevance
“…As can be seen in Figures 2, 3, 4, 6, and 7 of G07, component A is characterized by a spectral slope between f −1 and f −2 . Our Figure 1a displays the dynamic spectrum of the data recorded on day 2005‐357 (23 December 2005), when this variable low‐frequency noise and the SKR are well visible.…”
Section: Skr Spectrum Classification and Subcomponentsmentioning
confidence: 80%
See 2 more Smart Citations
“…As can be seen in Figures 2, 3, 4, 6, and 7 of G07, component A is characterized by a spectral slope between f −1 and f −2 . Our Figure 1a displays the dynamic spectrum of the data recorded on day 2005‐357 (23 December 2005), when this variable low‐frequency noise and the SKR are well visible.…”
Section: Skr Spectrum Classification and Subcomponentsmentioning
confidence: 80%
“…The most plausible origin for this noise is plasma impact noise on the spacecraft and antennas in f −2 , as described by Meyer‐Vernet [1985] and Meyer‐Vernet and Perche [1989], and possibly also f −1 noise. The level of the plasma impact noise spectrum depends on the plasma temperature, the presence of beams; thus the thin and thick morphology of component A described by G07 simply reflects the variability of the local plasma conditions.…”
Section: Skr Spectrum Classification and Subcomponentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cassini mission provided new results concerning the radiation directivity which is directly related to the emission beam pattern. Galopeau et al [2007b] analyzed the spectral shape of the SKR and showed that the radiation may be considered as the overlapping of hollow cones related to three components. Hence, using radio horizon technique, Farrell et al [2005] brought out the presence of an emission source associated to the Saturnian kilometric radiation.…”
Section: Comparison With Terrestrial and Saturnian Radiationsmentioning
confidence: 99%
“…However, Cassini investigations also showed the complexity of the interpretation of the SKR observations and the corresponding emission beam which crucially depends on the geometrical conditions of the SKR source with regard to the observer. Galopeau et al [2007bGalopeau et al [ , 2009 addressed the problem about the ellipticity of the polarization of the Saturnian radiation, and Fischer et al [2009] revealed the presence of a strongly elliptically polarized emission when the Cassini spacecraft is at latitudes higher than 30 ∘ . This source was found to be confined to relatively low latitudes and close to midnight, in discrepancy with Voyager observations which reported a source location well away from the high-latitude dayside cusp region.…”
Section: Comparison With Terrestrial and Saturnian Radiationsmentioning
confidence: 99%